A fly in the ointment: Bringing the patient perspective to healthcare policy. Issue 5 (September 2016) - Morin, Angela
Patient-centred care and patient engagement are not the "flavour of the month" nor just buzz phrases. The role of the patient voice in the review of the Quality of Care Information Protection Act and the creation of the Health Information Protection Act 2016 (Bill 119) was significant and transformative. Engaging patients and families whether at the bedside in a hospital, at the decision-making table in a healthcare organization, or in the creation of policy at the provincial and national levels is changing our healthcare system.